2021
DOI: 10.1515/jpem-2021-0554
|View full text |Cite
|
Sign up to set email alerts
|

Weight changes of children in 1 year during COVID-19 pandemic

Abstract: Introduction The coronavirus disease 2019 (COVID-19) pandemic has changed everyday life. The Korean government urged schools to close as a measure of social distancing, and children and adolescents seemed to gain weight due to home confinement. We aimed to investigate the trends in weight changes in children during the pandemic period. Materials and Methods This retrospective study included 139 children aged between 6 and 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 22 publications
2
23
2
Order By: Relevance
“…It has been suggested that obesity, fast food consumption, and the consumption of growth-related health functional foods are factors accelerating the onset of puberty in Korean adolescents ( 25 ). The BMI of elementary school students has risen significantly over the past year, as the physical activity of adolescents has decreased, and their consumption of fast foods has increased as a result of COVID-19 ( 26 ). Meanwhile, the immune-related health functional food industry is experiencing a boom that is unprecedented ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that obesity, fast food consumption, and the consumption of growth-related health functional foods are factors accelerating the onset of puberty in Korean adolescents ( 25 ). The BMI of elementary school students has risen significantly over the past year, as the physical activity of adolescents has decreased, and their consumption of fast foods has increased as a result of COVID-19 ( 26 ). Meanwhile, the immune-related health functional food industry is experiencing a boom that is unprecedented ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…3 Previous studies reported a correlation between life-style changes and weight gain/increases in body mass index (BMI), [4][5][6][7][8] while others showed changes in BMI during the COVID-19 pandemic. [9][10][11][12][13][14] Longitudinal studies of more than 100 000 healthy children in the USA 10,11 and Germany 12 revealed ≥2-fold changes in monthly BMI or BMI standard deviation scores (BMI-SDS) and age-and sex-adjusted BMI during the pandemic from pre-pandemic years.…”
Section: Coronavirus Disease 2019 (Covid-19) Was Initially Recognised Inmentioning
confidence: 99%
“…These changes in weight have affected individuals across the lifespan. In Korea, one study found that in the pediatric population, the proportion of overweight and obese children increased from 24.5% to 38.1% (p < 0.001) over only 1 year during the pandemic [25].…”
Section: Dietary Patterns and Weightmentioning
confidence: 99%